An Efficient DWT and Intuitionistic Fuzzy Based Multimodality Medical Image Fusion. Issue 2 (June 2017) - Soundrapandiyan, Rajkumar; Karuppiah, Marimuthu; Kumari, Saru; Kumar Tyagi, Sanjay; Wu, Fan; Jung, Ki‐Hyun
Abstract: Image fusion aims to integrate complementary information from multiple modalities into a single image with none distortion and loss of data. Image fusion is important in medical imaging, specifically for the purpose of detecting the tumor and identification of diseases. In this article, completely unique discrete wavelet transform (DWT) and intuitionistic fuzzy sets (IFSs) based fusion method (DWT‐IFS) is proposed. For fusion, initially, all source images are fused using DWT with the average, maximum, and entropy fusion rules. Besides, on the fused image IFS is applied. In the IFS process images are converted into intuitionistic fuzzy images (IFIs) by selecting an optimum value for the parameter in membership, non‐membership, and hesitation degree function using entropy. Then, the resulting IFIs are decomposed into the blocks, and the corresponding blocks of the images are fused using the intersection and union operations of IFS. The efficiency of the proposed DWT‐IFS fusion method is recognized by examining it with other existing methods, such as Averaging (AVG), Principal Component Analysis (PCA), Laplacian Pyramid Approach (LPA), Contrast Pyramid Approach (CPA), Discrete Wavelet Transform (DWT), Morphological Pyramid Approach (MPA), Redundancy Discrete Wavelet Transform (RDWT), Contourlet Transform (CONTRA), and Intuitionistic Fuzzy Set (IFS) using subjective and objective performance evaluation measures. The experimental results reveal that the proposed DWT‐IFS fusion method provides higher quality of information in terms of physical properties and contrast as compared to the existing methods.